231k views
5 votes
Which shows the correct substitution of the values a, b, and c from the equation 0 = – 3x2 – 2x + 6 into the quadratic formula?

2 Answers

3 votes

0=-3x^2-2x+6

Explanation:

A on edge2020

Which shows the correct substitution of the values a, b, and c from the equation 0 = – 3x-example-1
User Peter Verbeet
by
5.4k points
2 votes

For this case we have the following quadratic equation:


0 = -3x ^ 2-2x + 6

Where:


a = -3\\b = -2\\c = 6

The quadratic formula, to find the roots, is given by:
x = \frac {-b \pm \sqrt {b ^ 2-4 (a) (c)}} {2 (a)}

Substituting the values:


x = \frac {- (- 2) \pm \sqrt {(- 2) ^ 2-4 (-3) (6)}} {2 (-3)}\\x = \frac {2 \pm \sqrt {(- 2) ^ 2 + 4 (3) (6)}} {2 (-3)}

Answer:


x = \frac {2 \pm \sqrt {(- 2) ^ 2 + 4 (3) (6)}} {2 (-3)}

User Cmonkey
by
5.6k points